Explaining bank failures in the United States: The role of self-fulfilling prophecies, systemic risk, banking regulation, and contagion - Nils Herger (Swiss National Bank, Study Center Gerzensee, 2008)
Using count data on the number of bank failures in US states during the 1960 to 2006 period, this paper endeavors to establish how far sources of economic risk (recessions, high interest rates, inflation) or differences in solvency and branching regulation can explain some of the fragility in banking. Assuming that variables are predetermined, lagged values provide instruments to absorb potential endogeneity between the number of bank failures and economic and regulatory conditions. Results suggest that bank failures are not merely self-fulfilling prophecies but relate systematically to inflation as well as to policy changes in banking regulation. Furthermore, in terms of statistical and economic significance, the distribution and development of bankruptcies across US states depends crucially on past bank failures suggesting that contagion provides an important channel through which banking crises emerge.
Keywords: G21; G28; 330; bank failures; banking crisis; count data; Bankinsolvenz; Bankenkrise; Systemrisiko; Ansteckungseffekt; Bankenregulierung; Generalisiertes lineares Modell; Schätzung; USA